SIKAP DAN KEPUASAN PETANI TERHADAP ATRIBUT ASURANSI USAHATANI PADI DI KABUPATEN GARUT - Hardyanti, Putri Intan; Djuliansah, Dedi; Nuryati, Rina (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
Agricultural sector has a high level of risk and uncertainty caused by climate change, pest and disease attacks, floods, droughts, and price fluctuations. Includes the risk dan uncertainty of rice farming. As a risk management efforts, the government officially provides the Rice Farming Insurance program. This research aims to analyze farmer’s attitude and satisfaction to AUTP’s attributes with their correlation. This research located in Garut West Java. This research used survey method with 97 respondents AUTP’s member who benefited. Analysis tools that used in this research are Multiatribut Fishbein analysis, Customer Satisfaction Index (CSI), Importance Performance Analysis (IPA) and spearman’s rank correlation analysis. The results showed that the farmer’s attitudes to the AUTP’s attributes is neutral categories (227,14) and farmer’s satisfaction level to AUTP’s attributes is satisfy categories (74,4%). The most important attributes according to people attribute’s items Penyuluh Pertanian Lapangan (PPL) and promotion attribute’s items direct socialization. Farmer’s attitude and satisfaction to AUTP’s attributes has a very close correlation.